Vitamin D status among female university students in Pakistan: Vitamin D in female university students - Akhtar, Saeed; Ismail, Tariq; Zafar, Sara; Wahid, Muqeet; Gilani, Syed Amir (Progress in Nutrition, 2019)
Increased prevalence of hypovitaminosis D and the genesis of a myriad associated maladies among a variety of population fractions have been a focus of the scientific community and health professionals. Present cross-sectional study aimed at assessing the levels of serum 25- hydroxyvitamin D [25(OH)D] among female university students (FUSs) in Pakistan. Students were recruited and evaluated for various socio-demographic parameters including skin color, veil status, previous disease history, sun exposure and dietary condition. Serum levels of 25(OH)D were determined and information on lifestyle variables were gathered to ascertain vitamin D deficiency (VDD) and its correlates. Significant difference in serum levels of 25(OH)D among females with dark skin (22 ng/ml) as compared to white skinned (35 ng/ml) subjects was noted suggesting skin pigmentation as a contributory determinant for vitamin D deficiency. Similarly, the results indicated low vitamin D levels among veil observing FUSs. Though, VDD has not been found to be severe as 25(OH)D levels remained >18.0 ng/ml in all groups, however extreme caution is needed to improve these concentrations to optimal levels. Speculation can be drawn from the results that VDD might be much higher among illiterate population groups suggesting further research to ascertain prevalence of VDD among populations from varied socio-economic tiers in Pakistan.